Research of the Hot-fit-tooth Process of Helical Countershaft - Zhida Kou; Bo Wang (Jixie chuandong)
The hot-fit-tooth process of helical gear countershaft is a new process developed by our company for the new platform product in recent years. By means of theoretical analysis and experimental verification, the determination of hot-fit temperature, the influence of heating on the metallographic structure and tooth profile and helical line of gear, the design principle of gear fixture, and the quantitative analysis of various influencing factors in the process of hot-fit on teeth are studied. Finally, the reasonable temperature range is determined，the mass production of the product is realized by design the non-standard fixture. The process is precise and controllable. There is no damage to the shaft and gears. The position error is small，the noise and damage to the shaft during the traditional countershaft cold press are avoided，which has great promotion significance.